REDD+ politics in the media: a case study from Vietnam - Pham Thu Thuy (Center for International Forestry Research, 2011)
Since 2009, CIFOR has initiated the Global Comparative Study of REDD+ in six countries: Bolivia, Brazil, Cameroon, Indonesia, Tanzania and Vietnam. In analysing national REDD+ policy arenas and emerging strategies, CIFOR researchers have developed five areas of work for each country. These include a country profile, media analysis, policy network analysis, strategy assessment and a fifth area of specific policy studies, to be determined by emerging research results. In 2010 we are publishing the first country profiles and media analyses.